Multiple-modified Low-Density Lipoprotein as Atherogenic Factor of Patients' Blood: Development of Therapeutic Approaches to Reduce Blood Atherogenicity - G. Nikifirov, Nikita; R. Zakiev, Emile; V. Elizova, Natalia; N. Sukhorukov, Vasily; N. Orekhov, Alexander (Current Pharmaceutical Design, 2017)
Generally, atherosclerosis first occurs by the way of accumulation of intracellular and extracellular lipids in the arterial intima. Foam cells, overloaded by lipids, are the essential harbinger of the coronary artery disease. It should be noted that lipids that are usually composed of bulk of the intracellular lipids found in human arterial cells originate from low-density lipoprotein (LDL) circulating in human blood. Nonetheless, many efforts to force cells to accumulate cholesteryl esters under the influence of native LDL have been unsuccessful. Whilst LDL modified in vitro (exposed to malondialdehyde, oxidized with ions of transition metals, acetylated, etc.) promoted accumulation of lipids in cells, all the attempts made for the sake of hunting down such LDLs in the bloodstream still do not provide confident conclusions. Therefore, a controversy arose: firstly, lipids from the cells of vascular wall have proved to be descending from LDL; secondly, foam cells do not form under the influence of native LDL in vitro (i.e. no visible intracellular lipid deposition observed); thirdly, chemically manipulated LDL seems to possess atherogenic properties. Acetylated LDL was not found in the bloodstream; similarly, the existence of oxidized LDL in the circulation remains controversial. Such a conundrum sparked a thorough investigation, leading to some interesting results. Modified desialylated LDL in human blood stream has been identified, which was able to promote lipid deposition in cultured cells. Such an LDL has been isolated, displaying atherogenic properties. The atherogenic LDL seems to deviate in multiple features from its non-atherogenic counterparts: carbohydrate, protein, and lipid moieties which were mangled. Such multiple LDL transformations take place in human blood stream and seem to denote a succession of events forcing the particle to become atherogenic: desialylation, lipid loss, shrinkage, rising of surface electronegative charge, etc. On top of the fat deposition in cells, multiple modifications of LDL as well as some other deleterious effects, like cell proliferation and fibrosis, seem to be part of the chain of events finally unfolding into a full-scale atherosclerotic lesion.
Keywords: desialylated LDL